Inventarization and Diversity Index of Gastropods in Meras Beach, Bunaken District, North Sulawesi - Rifki, Muhammad; Papu, Adelfia; Saroyo, Saroyo; Rengkung, Hizkia; Lukman, Ermas Isnaeni (Universitas Sam Ratulangi, 2025)
Gastropods play an important role in maintaining the balance of coastal ecosystems, particularly as detritivores that support nutrient cycling. Pantai Meras, located in North Sulawesi, has a complex coastal ecosystem that includes mangrove forests, seagrass beds, and coral reefs, which support high biodiversity. However, information regarding gastropod diversity in this area remains limited. This study aims to identify gastropod species and analyze their diversity levels in the waters of Pantai Meras. A purposive sampling method was used for data collection, employing 0.5 m × 0.5 m plots placed randomly at 45 sampling points across three research stations with different substrate types, namely sandy substrate (Station 1), muddy sand substrate (Station 2), and sand mixed with coral fragments (Station 3). Data were analyzed using PAST software version 4.17 to calculate the Shannon diversity index (H’). The results showed a total of 243 gastropod individuals belonging to 89 species from six orders, with Neogastropoda being the dominant order, comprising 59 species. The most abundant species was Nassarius globosus, with a total of 26 individuals recorded. The overall Shannon diversity index (H') was 4.14, which falls into the high diversity category. The highest H' value was recorded at Station 1 (4.08), followed by Station 3 (4.02), and the lowest at Station 2 (3.43). The high gastropod diversity at Pantai Meras indicates that the coastal ecosystem in this area is still in good condition and capable of supporting sustainable gastropod populations. Environmental factors such as temperature, salinity, as well as the presence of mangroves, seagrass beds, and coral reefs contribute to the high species diversity of gastropods in the study area.